The message of holiness : restoring God's masterpiece - Tidball, Derek (Downers Grove, IL : InterVarsity Press, 2010)
Derek Tidball surveys the Scriptures for a comprehensive biblical understanding of this elusive mandate from God to "be holy as I am holy." The triune God of glory, he contends, sets us on paths that lead us through encounters with God, ourselves, our enemies and our companions to our ultimate destination, where we discover that we have been reshaped by God into his own image. --from publisher description
Part 6. The destination of holiness : To be like him (1 John 2:28-3:10) -- He will do it (1 Thessalonians 5:23-24). Study guide.
Includes bibliographical references (p. 13-19).
Keywords: Holiness -- Biblical teaching; Holiness -- Christianity